The evaulation of advertising objectives: Draft for discussion - Corkindale, David; Kennedy, Sherril (Cranfield School of Management, 1974)
This report is a sequel to that prepared earier by the MCRC on 'Setting Advertising Objectives' (Report no. 6). In this earlier work the need for setting clear advertising objectives was recommended as a necessary precursor for any measurement of advertising achievement. the different types of advertising objectives that can be set, and the circumstances in which they are set, was examined by the MCRC through in-depth analyses of some 27 product case histories. A clear distinction was drawn between marketing objectives.